KAPABILITAS DINAS TENAGA KERJA DALAM MENGATASI MASALAH KETENAGAKERJAAN DI KABUPATEN SIDOARJO - Betania Anggi Prafika; Arimurti Kriswibowo (Jurnal Ilmu Sosial dan Ilmu Politik)
Less than optimal absorption of labour can affect the occurrence of the unemployment phenomenon. Unemployment is one of the labour problems that occur in every country and region in it. Sidoarjo Regency is one of the districts that has had the highest Open Unemployment Rate in East Java Province for several consecutive periods. In overcoming these problems, an important role is needed from the Sidoarjo Regency Manpower Office as a leading sector in responding to the labour issues. This study aims to describe the capability of the Manpower Office to reduce unemployment in Sidoarjo Regency. The research method used is qualitative. The results of this study focus on six indicators, namely institutional, policy implementation, human resources, technical resources, financial system, and leadership. The results showed that the capability of the Sidoarjo Regency Manpower Office was considered quite successful in reducing unemployment. However, there were still some obstacles in the aspects of human resources and technical resources.